PENGARUH CITRA MEREK TERHADAP PERSEPSI CITARASA - E Rindangi Putri Hermanto; Haryanto Fadholan Rasyid (Proyeksi: Jurnal Psikologi, 2010)
This research investigated the effect of brand image on taste perception. The hypothesis of this research was that brand images would affect taste perception. It was also hypothesized that more qualified brand would result in more positive taste perception than less qualified brand. Product used in this research was mineral water. Two brands chosen for this research were A-one which represent more qualified brand, and A-two which represent less qualified brand (compared to A-one). Apart from these two brands, a non-branded package was also used. The samples (N = 60) were undergraduate student of the Faculty of Psychology,   a State Own University in Jogyakarta, who volunteered as research subjects. The samples were assigned to evaluate the taste of mineral water served in the three different brand packages. A taste perception scale was employed to collect  data through a counter-balance experimental design method. Experimental method with counter-balance design was conducted to ensure that the different in taste perception was the result of different brand images. Result revealed that brand image had effect on taste perception (F = 12,824, p<0,01). Branded package elicited positive response more than non-branded package. Thus, it causes more positive taste perception. Different result was obtained for more qualified brand and less qualified brand. There was no difference between more qualified brand and less qualified brand on taste perception.  This study concluded, due to similarity of the brands character, samples intend to have the same taste perception on the brands. Keywords: taste perception, brand images